The future of tourism in Zimbabwe: towards sustainability? - Mkono, Muchazondida (Cognizant Communication Corporation, 2021)
Before the political events after 2000, notably the Land Reform Program, Zimbabwe was a leading tourism destination in the Southern African region. However, political upheavals and consequent economic crises in the last decade damaged the attractiveness of the country as a tourist destination. Arrivals dropped drastically as the country was seen as unsafe for tourists. With the recent formation of the inclusive government in September 2008, and the gradual stabilization of the political and economic environments, it is hoped that the country's tourism industry can be restored to its former competitiveness. This article discusses the struggles and dilemmas that the tourism industry continues to face as it aspires towards sustainability.